Transient small bowel intussusception in a 30-year-old male - Francesk Mulita; Levan Tchabashvili; Elias Liolis; Ioannis Maroulis (Gastroenterology Review)
Intussusception is a process in which a segment of intestine invaginates into the adjoining intestinal lumen, causing bowel obstruction. It is a common paediatric surgery emergency, and it requires early diagnosis and treatment. Intussusception typically presents at between 6 and 36 months of age, and the male-to-female ratio is approximately 3 : 1. It is usually ileocolic, although other forms such as Ileo-ileal, jejuno-jejunal, jejuno-ileal, or colo-colic have also been described [1]. However, in adults the overall incidence of intussusception is around 2–3 cases per 1,000,000 of the general population annually, and it is usually secondary to an existing pathology [2, 3]. According to the literature, 30% of small bowel intussusceptions are caused by tumours, while 10% are idiopathic [4–6]. We herein report a case of a 30-year-old male with idiopathic transient small bowel intussusceptions.